Emotional States of Teenagers and Adolescents with Intact and Impaired Intelligence in Dangerous Situations Perception - Fatikhova, L.F.; Sayfutdiyarova, E.F. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2021)
The article is dedicated to the studying of emotional states in the structure of psychological security of teenage and adolescent students with both intact and impaired intellect. It is assumed that the development degree of emotional states, when students respond to dangerous situations, depends on the age and the intellectual impairments. The research engaged 157 teenagers (M=12,98 y.o.; SD=0,76 y.o.) and adolescents (M=16,27 y.o.; SD=0,69 y.o.). Some students had an intact intellect, whereas a number had an impaired intellect. The study used a questionnaire aimed at defining of the type of danger response by V.G. Maralov (2012). The research applied the work of the Emotional Attitude of Teenagers to Dangerous Situations (L.F. Fatikhova, E.F. Saifutdiyarova, 2021) aimed at the revealing of the emotional attitude to situations that threaten the life and health and to favourable situations. Present study also uses the work Teenagers in Dangerous Situations (L.F. Fatikhova, E.F. Saifutdiyarova, 2020) aimed to study the ability to recognize emotional states in people located in dangerous situations. The study revealed difficulties in the identification of emotional states and recognize emotions of participants of hazardous situations for teenagers with intellectual impairments compared to their intact-intellect peers. The impaired intellect teenagers prove to have a lower diversity of emotions and difficulties to communicate their emotions verbally in case of danger. Mann–Whitney test revealed that teenagers and adolescents with intact and impaired intellect show different emotional attitude to dangerous situations and ability to recognize emotions of endangered people. The obtained findings can be applied when developing programs aimed at forming in teenagers and adolescents the ability to reasonably perceive and respond to dangerous situations with regards to their age and intellectual impairment Статья посвящена проблеме исследования эмоциональных состояний в структуре психологической безопасности учащихся подросткового и юношеского возраста с сохранным и нарушенным интеллектом. Была выдвинута гипотеза исследования о том, что сформированность эмоциональных состояний при восприятии учащимися опасных ситуаций зависит от возраста и наличия нарушений интеллекта. В исследовании, в котором приняли участие 157 детей подросткового (M=12,98 лет; SD=0,76 лет) и юношеского возраста (M=16,27 лет; SD=0,69 лет) с сохранным и нарушенным интеллектом, были использованы: Опросник на выявление типа отношения к опасности В.Г. Маралова (2012); методика «Эмоциональное отношение подростков к опасным ситуациям» (Л.Ф. Фатихова, Е.Ф. Сайфутдиярова, 2021), направленная на выявление эмоционального отношения к опасным для жизни, здоровья и благополучия ситуациям; методика «Подростки в опасных ситуациях» (Л.Ф. Фатихова, Е.Ф. Сайфутдиярова, 2020), предназначенная для изучения способности к распознаванию эмоциональных состояний людей, находящихся в опасной ситуации. Выявлены трудности идентификации своих эмоциональных состояний, распознавания эмоций участников опасных ситуаций, меньшее разнообразие эмоций, трудности выражения эмоций на вербальном уровне у подростков с нарушениями интеллекта в сравнении с их сверстниками с сохранным интеллектом. Критерий Манна–Уитни показал различия в показателях эмоционального отношения к опасным ситуациям и распознавания эмоций участников опасных ситуаций у представителей подросткового и юношеского возраста с сохранным и нарушенным интеллектом. Полученные данные могут быть использованы при разработке программ по формированию способности подростков и лиц юношеского возраста адекватно воспринимать опасные ситуации и реагировать на них с учетом возраста и фактора сохранности / нарушения интеллекта.